Cardiovascular system adaptation of young elite athletes trained in different sports - Larins, V.; Pontaga, I. (Archivos de medicina del deporte, 2008)
In many sports performance depends on cardiovascular system adaptation to used training and competitions loads. Adaptation process becomes evident with changes in cardiovascular parameters at rest and at physical load. The nature and size of these changes are very important for young athletes` health and achievements. Therefore the aim of our research was to estimate the heart structural and functional characteristics and cardiovascular system adaptation of young elite athletes trained in different sports. Methods: The structural cardiac adaptation was estimated by echocardiography (Vivid 4, GE). The heart functional adaptation to the endurance training was determined on a cycle ergometer. The intensity of the exercises increased step by step from 0.5 to 2 W/kg, the exercise intensity - heart rate relationship was determined. Twenty 21,3±4,5 years old elite winter biathlon skiers, fourteen 18,3±4,3 years old cyclists and fi fteen 17,3±0,8 years old male basketball players participated in the investigation. Results: The largest heart stoke volumes were observed with cyclists (96.2± 16.2 cm3), a little smaller - with winter biathlon skiers (91.3±13.5 cm3). Basketball players had the largest heart volume in the end of the diastole. Nevertheless, their stroke volume was smaller (76.7 ± 15.7 cm3) in comparison with the athletes trained in endurance sports (p<0,05). Basketball players had higher heart rate values than the cyclists and athletes trained in winter biathlon during the same intensity exercises. The heart rate increase with growth of the power of exercises with basketball players was faster than with the athletes trained in biathlon and cycling. Conclusion: Echocardiography characteristics of all athletes did not exceed the upper limits for trained males. The data confi rm a better cardiovascular system adaptation to endurance exercises with the athletes trained in winter biathlon and cycling than with the young basketball players.